Catalogo de los Fulgoroidea (Homoptera) de Nicaragua - Maes, J.-M.=700 1 O'Brien, L.B.
(Es, Es)
Ilus., 81 ref.
Keywords: CLASIFICACION; FULGOROIDEA; HOMOPTERA; INSECTA; HUESPEDES; ENEMIGOS NATURALES; DISTRIBUCION GEOGRAFICA; NICARAGUA; REVISTA NICARAGUENSE DE ENTOMOLOGIA